Early-stage Lung Cancer Screening and Management (Springer Singapore, 2018)
This book discusses major issues and advances in the diagnosis and treatment of incidentally detected early-stage lung cancer (ESLC). In Part I, pathology and radiology experts comprehensively review the state-of-the-art advances in individual research fields, and offer an update on the cross-sectional anatomy of the lung and post-processing techniques for CT imaging. Part II focuses on the imaging features, differential diagnosis and radiologic-pathologic correlations of ESLCs in the categories pGGN, mGGN and solid nodules in compliance with the Guidelines on Lung Cancer Screening from the National Comprehensive Cancer Network (NCCN). Part III briefly introduces therapeutic management strategies for ESLCs, including surgical and non-surgical approaches, for instance stereotactic ablative radiation therapy (SABR) and radiofrequency ablation (RFA). Lastly, the authors have meticulously prepared 50 clinical cases of pathologically proven benign and malignant pulmonary nodules with in-depth discussion and experts' comments to further readers' understanding of practical imaging and management strategies of ESLCs.